2022
DOI: 10.3390/su14031217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Abnormal Climatic Events on the CPUE of Yellowfin Tuna Fishing in the Central and Western Pacific

Abstract: To explore the impact of climate change on fishery resources, the temporal and spatial characteristics of the thermocline in the main yellowfin tuna purse-seine fishing grounds in the western and central Pacific Ocean during La Niña and El Niño years were studied using the 2008–2017 Argo grid data (BOA_Argo) and the log data of commercial fishing vessels. A generalized additive model (GAM) was used to analyze the variables affecting yellowfin tuna fishing grounds. The results showed that in La Niña years, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This study found that among all climate data, the El Niño-Southern Oscillation (ENSO) index had the greatest impact on yellowfin tuna CPUE. This is consistent with the findings of Zhou et al [44], who observed that during El Niño events, yellowfin tuna CPUE shifted eastward, while during La Niña events, it shifted westward, thereby affecting the distribution of yellowfin tuna [45]. Additionally, this study found that the North Pacific Gyre Oscillation (NPGO) index is also one of the important features, while the Pacific Decadal Oscillation (PDO) index is not an important feature.…”
Section: Lasso Feature Selection and Analysis Resultssupporting
confidence: 92%
“…This study found that among all climate data, the El Niño-Southern Oscillation (ENSO) index had the greatest impact on yellowfin tuna CPUE. This is consistent with the findings of Zhou et al [44], who observed that during El Niño events, yellowfin tuna CPUE shifted eastward, while during La Niña events, it shifted westward, thereby affecting the distribution of yellowfin tuna [45]. Additionally, this study found that the North Pacific Gyre Oscillation (NPGO) index is also one of the important features, while the Pacific Decadal Oscillation (PDO) index is not an important feature.…”
Section: Lasso Feature Selection and Analysis Resultssupporting
confidence: 92%
“…The vertical overlap of bigeye tuna swimming depth and deep-set longline gear has a direct impact on bigeye catch rates in the Hawaii longline fishery [28,40,44,45]. With increasing ocean temperatures and ENSO events changing the thermal structure and oxygen concentration in different parts of the Pacific Ocean [7,29,33,46,47] and altering the spatial distributions of tuna species [6, 7, 11, 17-20, 28, 29], it is reasonable to expect that changes in climate factors would also impact tuna catch rates and spatial operations of the Hawaii longline fleet.…”
Section: Fishery Climate Change Climate Variability and Tuna Distribu...mentioning
confidence: 99%
“…In particular, spatial distribution of fishing is influenced by the interactions of "physical, biological, and economic mechanisms" [24]. Rising ocean temperatures and El Niño-Southern Oscillation (ENSO) events could influence the spatial distribution [1, 6, 7, 11, 17-20, 28, 29], abundance [1,7,9,17,20], and catchability [1,6,11,[19][20][21][30][31][32][33] of highly migratory species like tuna as different species have different spatial responses to climate change and variability due to their unique physiological adaptations and preferred habitats [6,19,[34][35][36]. As a result, fisheries that target different tuna species could be affected correspondingly by climate change and variability [6,19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is multicollinearity among marine environmental factors, which often leads these methods to overlook the spatial heterogeneity between the catch situations of yellowfin tuna in different ocean areas and changes in environmental factors or to omit some important influencing factors. Existing research frequently avoids the impact of limitations on model construction by limiting the scope of the research area or using limited fishing data from a specific commercial fleet [5,11,12,15,[17][18][19][20][21][22][23][24][25][26]. This artificially disconnects the spatial connection of yellowfin tuna resources, which is not conducive to the macro-analysis research of yellowfin tuna in ocean areas.…”
Section: Introductionmentioning
confidence: 99%